kk222
kk222
19-12-2017
Mathematics
contestada
Find the zeros of the function y= (x-2)(x+1)(x+3)
Respuesta :
jdoe0001
jdoe0001
19-12-2017
[tex]\bf y=(x-2)(x+1)(x+3)\implies 0=(x-2)(x+1)(x+3) \\\\\\ \begin{cases} 0=x-2\implies &~~2=x\\ 0=x+1\implies &-1=x\\ 0=x+3\implies &-3=x \end{cases}[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 68+ )
ACCESS MORE
Otras preguntas
Think about the terms of the bet. What are some things the lawyer asked for or studied while confined? Select all correct answers. novels puzzles languages game
Question: (Image Below)
Which choice correctly shows rounding to the hundredths place?
please answer this question
Which body can begin an impeachment process? the Senate the Supreme Court the State Department the House of Representatives
Find the value of x that will make A||B 9x + 4 5x + 20 x = [?]
1. Lee el siguiente texto y realiza una tabla donde clasifiques los diferentes sustantivos que encuentres: Estaba sentado en mi casa con mi amigo Patricio. Ya s
One of the reasons many new businesses fail is the owner’s lack of sound financial management. True False
m<1=(4x-7) and m<2=(x+12)
PLEASE ANSWER ASAP PLEASE! 20 POINTS! names of all organelles in the animal cell and their functions